1994
DOI: 10.1159/000227329
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor for the Treatment of Malignancies

Abstract: Tumor necrosis factor (TNF) is a cytokine produced in vivo by activated macrophages and monocytes with pleiotropic effects on normal and malignant cells. TNF is cytotoxic to several tumor cell lines in vitro and in vivo. Phase I and phase II trials have been conducted to determine toxicity to humans and to evaluate responses. Recent investigations will be reviewed. Despite promising results in vitro and in vivo, data from systemic administration in the treatment of malignancies have been disappointing. Local a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 40 publications
0
37
0
1
Order By: Relevance
“…Systemic TNF therapy for cancer patients, especially at high doses, can cause toxicity (7,8). Although cancer patients may already have high TNF levels at the onset of therapy, perhaps accounting in part for the added toxicity, the fact remains the therapeutic window for TNF may be narrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic TNF therapy for cancer patients, especially at high doses, can cause toxicity (7,8). Although cancer patients may already have high TNF levels at the onset of therapy, perhaps accounting in part for the added toxicity, the fact remains the therapeutic window for TNF may be narrow.…”
Section: Discussionmentioning
confidence: 99%
“…TNFR1 is ubiquitously expressed on all T cell populations, the entire lymphoid system, and most other cells. This explains TNF's systemic toxicity when used at high doses in oncology treatment and in diseases with normal TNF basal levels (7,8). TNFR2, in contrast, is more restrictively expressed, found only on select subpopulations of T cells, endothelial cells, neurons, and other occasional cells (9).…”
mentioning
confidence: 99%
“…In particular, locoregional treatment with TNF-a appears to be promising (Hieber and Heim, 1994) and is currently under investigation Klaase et al, 1995). In this study we describe an assay to determine the level of TNF-a in liver and tumour tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…systemically administered TNF-a before life-threatening toxicities set in, while tumour regression in mice required a dose of approximately 400 ,ug kg-' (Blick et al, 1987;McIntosh et al, 1988;Hieber and Heim, 1994). The maximum-tolerated dose of TNF-x depends on the route of administration.…”
mentioning
confidence: 99%
“…We have shown that in combination with hyperthermia or cryotherapy, TNF-a can induce significant tumor response (10,14). Unfortunately, systemic administration of TNF-a has dose-limiting toxicity (15,16). Therefore, there is a need for selective tumor delivery of TNF-a to minimize systemic toxicity.…”
Section: Introductionmentioning
confidence: 99%